Sistematização da rede de referência geodésica do Campus de Itaqui da Universidade Federal do Pampa - (:unkn) unknown (Universidade Federal do Pampa, 2020)
Geodetic networks, in addition to making topographic and geodetic activities and scientific projects more reliable and accurate, allow any user to obtain the precise coordinates of a point on the ground, increasing their productivity, facilitating and standardizing surveys and works in the field. Given this, this research developed the systematization of the geodesic reference network of the Itaqui campus of the Federal University of Pampa. This project carried out the transport of coordinates, both horizontal and vertical, through GNSS tracking and processing. We chose to use the SAT91989 physical landmark as a control point. After the screening, the obtained coordinates were transported to the other 11 vertices, also by the relative static method, in the form of a chain with an occupation time of not less than two hours, for the data processing the TopconTolls software was used. To obtain the altitudes, two distinct geometrical leveling circuits were carried out, starting from the RN1931B and RN1923T to the landmark at the entrance of UNIPAMPA. In the Unipampa area, leveling was carried out in the form of a chain, from vertex to vertex. A Local Topographic Plan (PTL) was generated using VT06 as the central vertex. The leveling circuits were classified as IN, since the closing error was less than -1.00 mm and the greater than 3.00 mm values allowed for this class according to NBR 13.133. The standard deviation of the coordinates of the vertices was also calculated and among the 11 (eleven) vertices tracked by the GNSS, the worst positional precision was 0.013 m for the VT10 vertex while the best precision was 0.009 m for the VT07. With the values found, individual monographs were made for the vertices, so that the data can be made available to the public. Contributing in this way, to the densification of the activities to be carried out.
Keywords: Redes geodésicas; Posicionamento GNSS; Sistema Geodésico Brasileiro; Geodetic networks; GNSS positioning; Brazilian Geodetic System; CNPQ::ENGENHARIAS